Assessing User Experience of a Mobile Application Using Usability Questionnaire Method - Syamsul Arifin; Lisa Maharani (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2021)
Eden Farm application is an application system used by customers to order vegetables and fruits. Eden Farm collaborates with hundreds of local farmers and dozens of raw material suppliers to provide all the culinary business needs of thousands of Eden Farm customers. However, there are still many who do not understand the usability of the Eden Farm application. In building a good system, one important part is good usability. Usability is closely related to user experience. User experience plays an important role in the development of a system, especially in the Eden Farm application, because user experience can show the ease that users feel and efficiency through user experience in using the system. The author tries to use the USE Questionnaire to 100 respondents. The analysis resulted in an average value of the Usefulness parameter of 85%. Then the parameter Ease of Learning with 82%, and Ease of Use with 80%, and the smallest is Satisfaction with 79%. These results indicate that the Eden Farm application is good. The results of measuring the usability of Eden Farm application with the classification